Glyoxalase‐1 Overexpression Reverses Defective Proangiogenic Function of Diabetic Adipose‐Derived Stem Cells in Streptozotocin‐Induced Diabetic Mice Model of Critical Limb Ischemia. (15th August 2016) - Peng, Zhiyou; Yang, Xinrui; Qin, Jinbao; Ye, Kaichuang; Wang, Xin; Shi, Huihua; Jiang, Mier; Liu, Xiaobing; Lu, Xinwu
Abstract: Adipose‐derived stem cell (ADSC)‐based therapy is promising for critical limb ischemia (CLI) treatment, especially in patients with diabetes. However, the therapeutic effects of diabetic ADSCs (D‐ADSCs) are impaired by the diabetes, possibly through intracellular reactive oxygen species (ROS) accumulation. The objective of the present study was to detect whether overexpression of methylglyoxal‐metabolizing enzyme glyoxalase‐1 (GLO1), which reduces ROS in D‐ADSCs, can restore their proangiogenic function in a streptozotocin‐induced diabetic mice model of CLI. GLO1 overexpression in D‐ADSCs (G‐D‐ADSCs) was achieved using the lentivirus method. G‐D‐ADSCs showed a significant decrease in intracellular ROS accumulation, increase in cell viability, and resistance to apoptosis under high‐glucose conditions compared with D‐ADSCs. G‐D‐ADSCs also performed better in terms of migration, differentiation, and proangiogenic capacity than D‐ADSCs in a high‐glucose environment. Notably, these properties were restored to the same level as that of nondiabetic ADSCs under high‐glucose conditions. G‐D‐ADSC transplantation induced improved reperfusion and an increased limb salvage rate compared D‐ADSCs in a diabetic mice model of CLI. Histological analysis revealed higher microvessel densities and more G‐D‐ADSC‐incorporated microvessels in the G‐D‐ADSC group than in the D‐ADSC group, which was comparable to the nondiabetic ADSC group. Higher expression of vascular endothelial growth factor A and stromal cell‐derived factor‐1α and lower expression of hypoxia‐induced factor‐1α were also detected in the ischemic muscles from the G‐D‐ADSC group than that of the D‐ADSC group. The results of the present study have demonstrated that protection from ROS accumulation by GLO1 overexpression is effective in reversing the impaired biological function of D‐ADSCs in promoting neovascularization of diabetic CLI mice model and warrants the future clinical application of D‐ADSC‐based therapy in diabetic patients. Stem Cells Translational Medicine 2017;6:261–271